Reason and fairness : constituting justice in Europe, from medieval canon law to ECHR - Müssig, Ulrike (Legal history library, 2019)
Throughout Europe, the exercise of justice rests on judicial independence by impartiality. In Reason and Fairness Ulrike Müßig reveals the combination of ordinary judicial competences with procedural rationality, together with the complementarity of procedural and substantive justice, as the foundation for the 'rule of law' in court constitution, far earlier than the advent of liberal constitutionalism. The ECHR fair trial guarantee reads as the historically-grown consensus of the functional judicial independence. Both before historical and contemporary courts, justice is done and seen to be done by means of judgements, whose legal requirements combine the equation of 'fair' and 'legal' with that of 'legal' and 'rational.' This legal determinability of the judge's fair attitude amounts to the specific (rational) European idea of justice.